1999
DOI: 10.1152/jappl.1999.87.4.1448
|View full text |Cite
|
Sign up to set email alerts
|

Response to inspiratory resistive loading during sleep in normal children and children with obstructive apnea

Abstract: The response to inspiratory resistance loading (IRL) of the upper airway during sleep in children is not known. We, therefore, evaluated the arousal responses to IRL during sleep in children with the obstructive sleep apnea syndrome (OSAS) compared with controls. Children with OSAS aroused at a higher load than did controls (23 +/- 8 vs. 15 +/- 7 cmH(2)O. l(-1). s; P < 0.05). Patients with OSAS had higher arousal thresholds during rapid eye movement (REM) vs. non-REM sleep (P < 0.001), whereas normal subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
6

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 24 publications
1
40
0
6
Order By: Relevance
“…AEP changes post-treatment of OSAS did not correlate with OSAS improvement as measured by AHI reduction (r ¼ 20.246; P ¼ 0.557) (16).…”
Section: Sleep Aepmentioning
confidence: 87%
“…AEP changes post-treatment of OSAS did not correlate with OSAS improvement as measured by AHI reduction (r ¼ 20.246; P ¼ 0.557) (16).…”
Section: Sleep Aepmentioning
confidence: 87%
“…Thus, whereas the rate of obstructive events per hour of sleep (apnea-hypopnea index [AHI]) allows for quantification of changes in upper airway obstruction for REM sleep, other measures are needed to assess upper airway obstruction during NREM sleep. It has been demonstrated previously that the inspiratory time relative to the duration of the respiratory cycle, the inspiratory duty cycle, increases linearly with the degree of upper airway obstruction 2224. Therefore, we determined the effect of TNI on upper airway obstruction in children by assessing both the AHI and the inspiratory duty cycle.…”
mentioning
confidence: 99%
“…Studies in children with OSA have confirmed a higher tendency of the upper airway to collapse compared to agematched controls [1,2]. This tendency is complicated by the fact that sleep apnoeic children are less likely to arouse in response to upper airway obstruction or to the apnoeaassociated hypercapnia [2,3].…”
Section: Definition Aetiology and Pathophysiologymentioning
confidence: 99%